2018
DOI: 10.1002/anie.201811053
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium(I) Halide versus Magnesium Metal: Differences in Reaction Energy and Reactivity Monitored in Reduction Processes of P−Cl Bonds

Abstract: Magnesium(I) halides (MgIX; X=Cl, Br, I), as high temperature molecules, are trapped and finally stored at −80 °C in toluene/donor solutions. These solutions provide insights into the fundamental mechanism of reduction reactions using activated magnesium metal as a prototype for every base metal. The most important example of such a reaction is the preparation of Grignard reagents (RMgX). The details of this highly complex mechanism especially of intermediates between Mg metal and MgII (RMgX) remain unknown un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The molecular compounds described thus far continue to play an important role in Ae-mediated bond activation and catalysis, and this is consistent with the recent surge in interest regarding the study of Ae metal complexes as cost-effective mediators for important organic transformations [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Indeed, compounds containing Ae-R functionalities also facilitate energy-relevant bond activation events.…”
Section: Introductionsupporting
confidence: 69%
“…The molecular compounds described thus far continue to play an important role in Ae-mediated bond activation and catalysis, and this is consistent with the recent surge in interest regarding the study of Ae metal complexes as cost-effective mediators for important organic transformations [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Indeed, compounds containing Ae-R functionalities also facilitate energy-relevant bond activation events.…”
Section: Introductionsupporting
confidence: 69%
“…Mg + -halides have been studied in comparison with magnesium metal as reducing agents, for instance in the reaction with P-Cl bonds [26]. The same reference mentions also relatively stable (with respect to disproportionation into Mg 0 and Mg 2+ species) biradical species such as [MgBr(N n Bu 3 )] 2 and metalloid clusters like the anionic [Mg 16 Cp* 8 Br 4 K] -, whose proposed structure was calculated to possess multiple Mg-Mg bonds.…”
Section: Magnesiummentioning
confidence: 99%
“…Since their isolation, the magnesium­(I) complexes have been demonstrated to be powerful reducing reagents in small-molecule activation and organometallic synthesis . Mononuclear magnesium­(I) species are proposed as intermediates in the formation of the Mg–Mg compounds and in small-molecule activation. , Until now, no stable mononuclear magnesium­(I) compounds have been isolated, although Schnöckel et al showed that the metastable donor-stabilized magnesium­(I) halides could be obtained in solution at low temperature. , …”
mentioning
confidence: 99%
“…6,17 Until now, no stable mononuclear magnesium(I) compounds have been isolated, although Schnockel et al showed that the metastable donor-stabilized magnesium(I) halides could be obtained in solution at low temperature. 18,19 Very recently, Ren et al 20,21 and Gilliard et al 22 reported the magnesium-bipyridine and -diazo complexes D−G. Analyses of the electronic structures reveal that the bipyridine and diazo ligands are in a radical anion state due to the redox-active properties, and the magnesium center is essentially in the +2 oxidation state.…”
mentioning
confidence: 99%